Measurement of the semileptonic b branching fractions and average b mixing parameter in Z decays - Abreu, P; Adam, W; Adyc, T; Adzic, P; Ajinenko, I; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; et al. (2001)
The semileptonic branching fractions for primary and cascade b decays BR(b → l-), BR(b → c → l+) and BR(b → c̄ → l- were measured in hadronic Z decays collected by the DELPHI experiment at LEP. The sample was enriched in b decays using the lifetime information and various techniques were used to separate leptons from direct or cascade b decays. By fitting the momentum spectra of di-leptons in opposite jets, the average b mixing parameter x̄ was also extracted. The following results have been obtained: (equation presented).